Mycorrhizal macrofungi diversity (Agaricomycetes) from Mediterranean Quercus forests; a compilation for the Iberian Peninsula (Spain and Portugal) - Ortega, Antonio; Lorite, Juan; Valle, Francisco (Nova Hedwigia, 2010)
A compilation study has been made of the mycorrhizal Agaricomycetes from several sclerophyllous and deciduous Mediterranean Quercus woodlands from Iberian Peninsula. Firstly, we selected eight Mediterranean taxa of the genus Quercus, which were well sampled in terms of macrofungi. Afterwards, we performed a database containing a large amount of data about mycorrhizal biota of Quercus. We have defined and/or used a series of indexes (occurrence, affinity, proportionality, heterogeneity, similarity, and taxonomic diversity) in order to establish the differences between the mycorrhizal biota of the selected woodlands. The 605 taxa compiled here represent an important amount of the total mycorrhizal diversity from all the vegetation types of the studied area, estimated at 1,500-1,600 taxa, with Q. ilex subsp. ballota (416 taxa) and Q. suber (411) being the richest. We also analysed their quantitative and qualitative mycorrhizal flora and their relative richness in different ways: woodland types, substrates and species composition. The results highlight the large amount of mycorrhizal macrofungi species occurring in these mediterranean Quercus woodlands, the data are comparable with other woodland types, thought to be the richest forest types in the world. We point out that the presence of genera that are very well adapted to sclerophyllous Mediterranean woodlands with a potential use in afforestation or recovery programs, or being rare species, are listed in the Regional Red List of Endangered Macromycetes. Since, these woodlands suffer heavy environmental pressure, human and climate mediated, we conclude many species are approaching a high extinction risk, and it is urgent to apply legal and management measures, both, of national (Spain and Portugal) and European governments.
The following values have no corresponding Zotero field: pub-location: Stuttgart publisher: Schweizerbart'sche Verlagsbuchhandlung
Keywords: affinity; conservation; diversity; mycorrhizal macrofungi; quercus woodlands